Design of a milli-newton force balance for hypersonic rarefied wind tunnel. (November 2021) - Wu, Chen-Wu; Liu, Cong; Hu, Deng-Liang; Liu, Hong-Li; Huang, He-Ji
Highlights: A novel micro-newton balance is conceptualized for hypersonic rarefied wind tunnel. Numerical analysis is conducted on the main part of the balance. Quasi-static calibration and in-situ calibration are carried through. Abstract: A multi-axial balance based on strain gauge was designed to measure the milli-newton gas-dynamic forces. The static and dynamic characteristics of the balance were analyzed by numerical method. The strain responses of the structure to static as well as transient loading were maintained by finite element analysis and the measuring capacity estimated. The quasi-static calibration was carried through with standard weights and the sensitivity coefficient obtained. Tentative experiments were conducted in a hypersonic rarefied wind tunnel and typical outcomes were demonstrated as preliminary validation of the design.